Diagnosis, Clinical Manifestations and Treatment of Lyme Disease - Jakubowska, Katarzyna; Janocha, Aleksandra; Jerzak, Aneta; Ziemba, Paweł (Quality in Sport, 2024)
Introduction and purpose Lyme disease was identified in the 1970s. It is an anthropozoonosis caused by spirochetes from the Borrelia family. This disease is the most common one caused by pathogens transmitted by ticks. It can manifest in various ways and typically progresses through three phases, each of which can present characteristic symptoms of infection. However, it often progresses asymptomatically. Antibiotics are widely used in the treatment of various forms of Lyme disease and demonstrate satisfactory efficacy. However, the most important aspect is the prevention of infections through personal protection against exposure. The aim of the article is to summarize information on Lyme disease, its risk factors, diagnosis, clinical manifestations, and treatment. Materials and methods The literature available in the PubMed database is searched using terms such as Lyme borreliosis and Lyme disease. Results Lyme disease is a moderately understood condition. Its risk factors have been studied, allowing us to identify those particularly at risk. However, despite this, the condition often presents diagnostic challenges, requiring considerable experience from clinicians. The disease can manifest in various ways, and antibiotics are an effective therapy in most cases. Despite numerous scientific studies on Lyme disease, not all pathophysiological mechanisms have been elucidated. Additionally, there is an ongoing debate regarding the validity of post-treatment Lyme disease syndrome (PTLDS). Conclusions Research on Lyme disease continues to provide new information, from diagnostics and clinical manifestations to treatment. Knowledge about infections caused by genospecies of the Borrelia family is extensive. However, there are still areas that are less well understood.